Recovery from stunting in early childhood and subsequent schooling outcomes: Evidence from NIDS Waves 1–5. Issue 3 (3rd May 2020) - Casale, Daniela
ABSTRACT: While an extensive literature documents the negative effects of stunting on children's developmental potential, there is far less evidence on whether a recovery from stunting in childhood – often referred to as 'catch-up growth'– helps mitigate the negative effects of early growth retardation. This paper explores the association between catch-up growth in early childhood and subsequent schooling outcomes using data from the first five waves of NIDS. The findings suggest that children who recovered from stunting in early childhood go on to complete fewer years of schooling compared to their non-stunted counterparts, driven in large part by a slower progression through school. However, there also appear to be heterogeneous effects depending on the extent of recovery; the small proportion of children who recovered substantially exhibit similar schooling outcomes to the non-stunted group. These results have important implications for the timing of nutritional (and other) investments in the early childhood period.